When Obedience and Resilience Become a Burden: Tadayyun, Academic Resilience, and Dual Role Conflict among Student-Mothers in Online Learning - Alifa Ashaira; Evi Afifah Hurriyati (International Journal Of Humanities Education and Social Sciences (IJHESS), 2026)
The rapid expansion of online higher education following the COVID-19 pandemic has significantly increased the participation of student-mothers, intensifying the challenges associated with balancing academic, domestic, and professional responsibilities. This situation has heightened the potential for multiple role conflict, particularly in relation to personal religiosity (tadayyun) and academic resilience as internal coping resources. Despite growing attention to work–family conflict, limited empirical research has examined how tadayyun and academic resilience jointly predict multiple role conflict among student-mothers engaged in online learning. This study aimed to analyze the role of tadayyun and academic resilience in predicting multiple role conflict among student-mothers participating in online higher education. A correlational research design was applied using multiple linear regression analysis. The sample consisted of 150 student-mothers selected through purposive sampling. Partial regression analysis indicated that tadayyun (β = 0.190; p < 0.05) and academic resilience (β = 0.650; p < 0.001) had positive and significant effects on multiple role conflict, with academic resilience identified as the strongest predictor. Simultaneous testing (ANOVA) produced an F-value of 114.747 (p < 0.001), confirming the statistical significance of the regression model. The coefficient of determination (R² = 0.610) showed that 61% of the variance in multiple role conflict was explained by tadayyun and academic resilience, while 39% was influenced by other factors beyond the model. These findings demonstrate that tadayyun and academic resilience collectively exert a substantial predictive influence on multiple role conflict among student-mothers in online learning contexts. Future research is encouraged to include more diverse populations and explore additional mediating or moderating variables to better understand the dynamics of role conflict in higher education.